SIRT7-Induced PHF5A Decrotonylation Regulates Aging Progress Through Alternative Splicing-Mediated Downregulation of CDK2 - Yu, Ai Qing; Wang, Jie; Jiang, Shi Tao; Yuan, Li Qun; Ma, Hai Yan; Hu, Yi Min; Han, Xing Min; Tan, Li Ming; Wang, Zhi Xiao (Frontiers in Cell and Developmental Biology, 2021)
Dysregulation of protein post-translational modification (PTM) can lead to various pathological conditions, such as sperm development defects, malignant transformation, depression, and ageing. SIRT7 is a NAD + dependent protein deacetylase. Besides known deacetylation, SIRT7 may also have the capacity to remove other acylation. However, the roles of SIRT7-induced other de-acylation in ageing is still largely unknown. Here, we found that the expression of SIRT7 was significantly increased in senescent fibroblasts and aged tissues. Knockdown or overexpression of SIRT7 can inhibit or promote fibroblast senescence. Knockdown of SIRT7 led to increased pan- lysine crotonylation (Kcr) levels in senescent fibroblasts. Using modern mass spectrometry (MS) technology, we identified 5149 Kcr sites across 1541 protein in senescent fibroblasts, providing by far the largest crotonylome dataset in senescent cells. Specifically, among the identified protein, we found SIRT7 de-crotonylated PHF5A, an alternative splicing factor, at K25. De-crotonylation of PHF5A K25 contributed to decreased CDK2 expression by Retained Intron (RI) induced abnormal alternative splicing, thereby accelerating fibroblasts senescence, supporting a key role of PHF5A K25 de-crotonylation in ageing. Collectively, our data revealed the molecular mechanism of SIRT7-induced k25 decrotonylation of PHF5A regulating aging, and provide new ideas and molecular targets for drug intervention in cellular ageing and the treatment of aging-related diseases, indicating that protein crotonylation has important implication in the regulation of ageing progress.